2019
DOI: 10.1017/jie.2018.3
|View full text |Cite
|
Sign up to set email alerts
|

Transformative Learning: A Precursor to Preparing Health Science Students to Work in Indigenous Health Settings?

Abstract: Australian undergraduate programmes are implementing curriculum aimed at better preparing graduates to work in Indigenous health settings, but the efficacy of these programmes is largely unknown. To begin to address this, we obtained baseline data upon entry to tertiary education (Time 1) and follow-up data upon completion of an Indigenous studies health unit (Time 2) on student attitudes, preparedness to work in Indigenous health contexts and transformative experiences within the unit. The research involved 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 33 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…If these are indeed the skills with potential for equipping individuals to interoperate in intercultural settings, they may also be the skills with potential for enacting decoloniality. For example, extant literature specific to the complex Australian Indigenous studies space points to the occurrence of critical reflection within curricula based on decolonial intentions and the experience of transformative learning (Bullen & Roberts, , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these are indeed the skills with potential for equipping individuals to interoperate in intercultural settings, they may also be the skills with potential for enacting decoloniality. For example, extant literature specific to the complex Australian Indigenous studies space points to the occurrence of critical reflection within curricula based on decolonial intentions and the experience of transformative learning (Bullen & Roberts, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The unit, delivered at a large Australian university, is on Indigenous and cross‐cultural psychology and is designed to promote cultural capabilities within undergraduate psychology students. Of note, this core third‐year unit follows delivery of a core inter‐professional first year unit on Indigenous cultures and health behaviors designed to support students development of foundational cultural capabilities with specific reference to Indigenous Australians (for an overview of this first year unit, inclusive of curricular, pedagogical, and assessment models in the context of critical reflexivity and transformative learning, see Bullen & Roberts, ). Importantly, this first year unit is typically students’ first exposure to models of critical reflexivity and (for the vast majority), to Indigenous knowledge, perspectives and people.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into consideration that these workshops indicate an improved cultural humility, findings suggest that, while cultural safety programmes can lead to these short-term improvements (Durey, 2010), one-off workshops may not be sufficient for promoting ongoing knowledge and attitudinal changes required for culturally safe practice. Indeed, a recent study by Bullen and Roberts (2018) found that an entire 1st year learning unit dedicated to Indigenous Australian cultures and health only brought about small but measurable changes in students' attitudes and preparation towards working with Indigenous Australians. According to Gibbs (1984), it is difficult for a person to fully understand the value system of another culture unless he/she is brought up in, or has lived in, that culture for a long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…RAD processes and the transformative properties of the Indigenous pedagogy (Bullen and Roberts, 2018 a , 2018 b ) ignited student interest and passion to work with Aboriginal and Torres Strait Islander peoples. The process of transformational learning is theorised by a shift in the way we understand and make sense of our world which starts with a process or experience that ignites new ways of sense making and then ‘subsequent understanding, appreciation and action’ (Mezirow, 1990, p. 1).…”
Section: Discussionmentioning
confidence: 99%